THE INFLUENCE OF THE AL-QURAN ON THE CHARACTER OF CHILDREN - Muhammad Suganda Triadi; Arif Prasetio (Proceeding International Seminar of Islamic Studies, 2022)
To form a balanced, healthy and strong human character (Character building), it is strongly influenced by religious education, especially Islam. The placement of the basics of religious education is an obligation for parents and is a duty for teachers, the community, and the government by carrying out various activities and educational institutions. This paper discusses the influence of the Koran on the character of children. Education is an ongoing process that will determine the character of the nation in the present and in the future. A nation will emerge as a nation with good character or not, depending on the quality of its education. There are many methods to shape children's character, one of them is by using the Al-Quran education approach. In addition to being part of the process of forming noble character, it is expected to be able to form the main foundation in increasing the degree and dignity of children as children of the nation. Character education should be carried out comprehensively, covering all aspects of education, starting from the preparation of children from birth to efforts to strengthen children's physical and spiritual abilities. Because in truth, every child is born with His nature. With this nature, children have the potential to be educated, cared for, and with great opportunities to develop and increase their abilities in terms of knowledge and skills, so that a person with good moral character is formed, and has behavior according to the teachings of the Qur'an and Sunnah. However, this character education is not something that is instant and requires a fairly long process, as long as habituation and cultivation is carried out in the environment of the child or student.Keywords: Children's Character, Al-Quran Education